Health Consequence of Gas Filling on the Workers’ Health of Two Cities in Iraq (Comparative Study) - Hussein Ali Mohammed 1 , Wijdan Abdulameer Kamel 2 , Abid Salih Kumait 3 (Institute of Medico-legal Publications Pvt Ltd, 2021)
A gas is a sample of matter that conforms to the shape of a container in which it is held and acquires a uniformdensity inside the container, even in the presence of gravity and regardless of the amount of substance in thecontainer. If not confined to a container, gaseous matter, also known as vapor, will disperse into space . Theterm gas is also used in reference to the state, or condition, of matter having this property.Aims: To identify the demographic data of the worker and to comparative beteen kirkuk gas filling companyand Tikrit gas filling company among work hazards like health, physical, chemical, physiological, mechanicalhazards.Methodology: Quantitative design (comparative study) was conducted for worker in company gas fillingin Tikrit (Salah aldin )and Kirkuk city the study was carried out from the 10th February 2020 to 13th Augst2020. This study was conducted in Kirkuk city and Tikrit (Salah aldin ). The present study was conductedin two company of gas filling:Company gas filling / branch Kirkuk and Company gas filling / branch salahEldin. The data was prepared, organized and coded into the computer file; Statistical Package for SocialScience (SPSS) version (24) was used for data analysisResults the result of demographic data for both kirkuk and Tikrit city shows that the age group (20-29years) represents a high percentage in the Kirkuk gas and Tikrit city and represent (40.0%) and (38.0%)respectively , with regard to the gender the results shows high percentage from gender were male in kirkukand tikrit and represent (95.0% )and (98.0%) respectively ,also the result shows the kirkuk workers weremore less effected than tikrit workers also the results shows the chemical ,mechanical and psychosocialhazard was effect in tikrit workers more than kirkuk workers .